Konstruksi Mutan Pseudomonas sp. untuk Meningkatkan Produksi Indole Acetic Acid (IAA) melalui Mutagenesis dengan Transposon - Aris Tri Wahyudi; Mutiha Panjaitan; Nisa Rachmania (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2009)
Pseudomonas sp. is one of bacterial groups having ability to promote plant growth and health. Of a hundred successfully isolated Pseudomonas sp. from soybean rhyzosphere, 98 were found to produce indole acetic acid (IAA) ranging from 0.33 to 16.02 ppm. These isolates are bacilli, motile, Gram negative, and showing positive oxidase assay. One of them, i.e. Pseudomonas sp. CRB17, can promote plant growth by means of significant stimulation of primary root length and lateral root number. This isolate was then subject to mutagenesis using transposon Mini-Tn5Km1 to increase IAA production. Mutagenesis was done by conjugation between E coli S17-1 (l pir) carrying transposon mini-Tn5Km1 (donor) and Pseudomonas sp. (recipient), resulting in conjugation frequency of approximately 3.1 x 10-5 cell per recipient. The resulted CRB17 mutants were then tested for their ability to produce IAA, one of which showed an increment of IAA production up to 77.5%, while some others showed no significant change or even had a reduction to 55.3%.  Sequence analyisis of 16S rRNA gene of Pseudomonas sp. CRB17 indicated that it has a high homology with that of Pseudomonas plecoglossicida (identical value of 99%). The results recommends that mutagenesis using transposon can be applied to increase IAA production, especially in Pseudomonas sp. CRB17.